Marginal integrity and microleakage of direct and indirect composite inlays: SEM and stereomicroscopic evaluation Integridade e microinfiltração marginal de restaurações diretas e indiretas de compósitos: avaliação por estereomicroscopia e MEV - Carlos José Soares; Leonardo Celiberto; Paula Dechichi; Rodrigo Borges Fonseca; Luis Roberto Marcondes Martins (Sociedade Brasileira de Pesquisa Odontológica, 2005)
The aim of this study was to evaluate the microleakage of direct and indirect composite inlays by stereomicroscopy and scanning electron microscopy (SEM). Thirty bovine incisors were ground to obtain an incisal platform, simulating the occlusal surface of a human molar. Each tooth received two 8° proximal cavities with cervical finishing line prepared in dentine or enamel. One of the cavities was filled with Filtek Z250/Single Bond, using the direct technique, and the other was filled with with Solidex/Rely X ARC/Single Bond, using the indirect technique. The samples were stored in water at 37°C for 24 hours and placed in a 50% silver nitrate solution for 6 hours in a dark container. Next, the samples were washed under running water, immersed in a developing solution and exposed to fluorescent light for 12 hours. The teeth were then severed and evaluated for dye penetration by stereomicroscopy and SEM. There were no significant differences between the direct and indirect techniques for the cervical finishing line in enamel, but for the finishing line in dentin, the indirect technique allowed less microleakage than the direct technique. SEM analysis showed leakage similar to that observed by stereomicroscopic analysis. The use of stereomicroscopic and SEM evaluations improves microleakage analysis. O objetivo deste estudo foi avaliar a microinfiltração em restaurações diretas e indiretas em resina composta por meio de estereomicroscopia e microscopia eletrônica de varredura (MEV). Trinta incisivos bovinos foram lixados de forma a produzir uma plataforma incisal, simulando a face oclusal de um molar humano. Cada dente recebeu dois preparos proximais com 8º e término cervical em esmalte ou dentina. Uma cavidade foi restaurada pela técnica direta com Filtek Z250/Single Bond, e a outra pela técnica indireta com Solidex/RelyX ARC/Single Bond. As amostras foram armazenadas em água a 37°C por 24 horas e então imersas em solução de 50% de nitrato de prata por 6 horas em recipiente escuro. As amostras foram lavadas em água corrente, imersas em solução reveladora e expostas à luz fluorescente por 12 horas. Os dentes foram seccionados para avaliação da penetração do marcador em lupa estereoscópica e MEV. Não houve diferença entre as técnicas direta e indireta para o término em esmalte, porém, para o término em dentina, a técnica indireta resultou em menor infiltração. MEV mostrou infiltração similar à da lupa estereoscópica. A análise por meio de lupa estereoscópica e MEV melhora a avaliação da microinfiltração.